Organizational learning capacity of startups in Northeast Brazil (REGE Revista de Gestão, 2020)
Purpose – This empirical and exploratory study analyzed the role of interaction with the innovation environment and of the organizational learning capacity (OLC) development stage in startups in Northeast Brazil based on the perception of managers of these companies. Design/methodology/approach – This was a quantitative study. Questionnaires were sent electronically to the managers of startups in the nine states of Northeast Brazil. A total of 54 managers participated, composing a non-probabilistic sample. The data collected were analyzed by multiple linear regressions. Findings – The results obtained seek to evidence whether the interaction of startups in Northeast Brazil with the startup ecosystem and the development stage in which these companies are found are associated with OLC. The results confirmed the hypothesis that higher startup development stages are positively associated with higher levels of OLC in the sample. A negative association was identified between the manufacturing startup type and the OLC level, and the level of interaction with the innovation environment was still infrequent. Research limitations/implications – This study contributes to the literature on the determinants of organizational learning and to startup managers who wish to more effectively promote this learning. Implications of the findings are discussed. Practical implications – This study contributes to the literature on the determinants of organizational learning and to startup managers who wish to more effectively promote this learning. Implications of the findings are discussed. Originality/value – Studies on Brazilian startups are still relatively scarce, especially studies that focus on learning capacity. No other studies addressing the hypotheses tested here were found.